2003
DOI: 10.1007/s11664-003-0245-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural effect on the creep strength of a Sn-3.5%Ag solder alloy

Abstract: INTRODUCTIONAs discussed by Morris and Reynold, 1 there is a large possibility that important mechanical properties, such as the creep strength of eutectic solder alloys, can change by orders of magnitude if the microstructure is altered. Morris et al. have performed vigorous research work 2-5 on the effect of microstructure, particularly the grain size effect, on the mechanical properties of Sn-Pb eutectic solder alloys and solder joints. Their studies show that, as the cooling rate during solidification incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 7 publications
5
17
0
Order By: Relevance
“…This shows that IMC particles at grain boundaries can severely limit boundary behaviors (GBS/GBD), as pointed out by previous studies. 18,19 The optical microscopy observations of the eutectic area yield similar results. In Fig.…”
Section: Small-scale Deformation Of Eutectic Regionsupporting
confidence: 60%
See 2 more Smart Citations
“…This shows that IMC particles at grain boundaries can severely limit boundary behaviors (GBS/GBD), as pointed out by previous studies. 18,19 The optical microscopy observations of the eutectic area yield similar results. In Fig.…”
Section: Small-scale Deformation Of Eutectic Regionsupporting
confidence: 60%
“…17 Such a fine dispersion of hard spherical IMC particles can enhance the creep resistance of the alloy by hindering the gliding of dislocations (dispersion hardening). 5,18 In order to observe the local deformation mechanism(s) of the SAC alloy, Vickers indentation was performed. Figure 4a shows an SEM image of a Vickers indent in the primary b-Sn region with ledges forming around it.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1-3 A number of papers have been published on Sn-Ag binary-alloy creep behavior measured with bulk samples. [4][5][6][7][8][9][10] For example, Huang et al 3 has shown that steady-state creep rates are controlled by dislocation-pipe diffusion in the tin matrix in a Sn-3.5Ag alloy. Choi et al showed that aging affects the secondary creep rates.…”
Section: Introductionmentioning
confidence: 99%
“…The present authors have also performed research on the creep and rupture behaviors of Cu wire/solder-joint specimens of Sn-3.5% Ag and Sn-0.5% Cu alloys and compared the results with those of the test specimens cut from the same alloy ingots. [5][6][7] …”
Section: Introductionmentioning
confidence: 99%